Complex search task: how to make a phone safe for a child - Rutter, Sophie; Blinzler, Verena; Ye, Chaoyu; Twidale, Michael B.; Wilson, Max L. (Rheinisch-Westfaelische Technische Hochschule Aachen, 2017)
There are many factors in task design that might make it ‘complex’: having multiple components, having multiple cross-dependent components, tasks that involve comparison, evaluation, estimation, or learning. In this paper, we discuss a case study of a complex task we may consider to be highly natural, a common concern for many people, and one that ‘should’ have a clear answer, but doesn’t: how do you make a phone safe for a child. For this question, there is a lot of opinion online, many possibilities for actions, many variations in hardware and software, but ultimately no one clear and correct answer for everyday phone users. We found very little objective behaviours that separated people in terms of performance but instead have begun to identify some successful tactics that are not directly linked to domain knowledge.